LA INTELIGENCIA ARTIFICIAL EN LAS ESTRATEGIAS DE MARKETING DE LAS MARCAS ECUATORIANAS - MUÑOZ GARCIA DAYRA DAYANNA (2024)
In Ecuador, digital marketing has advanced considerably, with companies adopting chatbots and data analytics to deliver individualized and effective experiences to customers. Industries such as finance and transportation are deploying AI to improve customer engagement and security. The problem to be inquired focuses on how AI influences the marketing strategies of Ecuadorian brands. This research is relevant because effective marketing strategies are vital to business growth and success in a competitive and ever-changing environment. The objectives are to analyze the impact on brand positioning, investigate the effectiveness of the tools and evaluate their application in marketing. The hypothesis suggests that integration significantly improves advertising performance, campaign personalization, and customer experience. The theoretical framework addresses background and studies on the use of AI in marketing. Globally, it has transformed marketing strategies, being adopted by 20% of leading companies. In Latin America, companies are beginning to see AI as essential to improve efficiency and personalization in marketing. In Ecuador, studies show that SMEs and large enterprises that have adopted report improvements in customization and operational efficiency, although they face challenges such as lack of technical knowledge and resistance to change. In addition, the use of AI has proven to be a key tool for audience segmentation and message personalization, optimizing resources and times. The positive response from customers indicates that AI can significantly improve the customer experience if implemented ethically.